OPTIMALISASI PERAN MAHASISWA DALAM FASILITASI PEMBUATAN NIB SECARA ELEKTRONIK DI DESA SALAMNUNGGAL KABUPATEN CIANJUR - Sely Puspita Hati,; Chika Oktavianti,; Jasmin Nur Amanda,; Ardiansyah Saputra,; Afnan Boby Suryadi, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The issuance of Business Identification Numbers (NIB) through the Online Single Submission (OSS) system, launched by the government to strengthen the legality of UMKM. The NIB through OSS is an official identity that must be possessed by every business operator in Indonesia. The lack of business legality is one of the main factors hindering the growth of Micro, Small, and Medium Enterprises (UMKM), particularly in the village of Salamnunggal, Cianjur Regency. The community service activities conducted by students from KKN 02 of Al-Ghifari University aim to address this issue. Additionally, these activities are designed to introduce, enhance knowledge, and assist UMKM operators in obtaining NIBs through the OSS website. The implementation method consists of five stages: survey, presentation of materials, data collection, assistance with NIB registration through OSS, and provision of physical evidence. The results of this activity show that UMKM operators in Salamnunggal Village have demonstrated improved understanding and awareness of the importance of legal status, which will facilitate access to capital, training, and government assistance, as well as enhance their overall business potential.